2012
DOI: 10.1155/2012/417247
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Characterisation of Genotypically Different Clones of MRSA in the Production of Biofilms

Abstract: The ability to adhere and produce biofilms is characteristic of enhanced virulence among isolates of methicillin-resistantStaphylococcus aureus(MRSA). The aim of the study is to find out whether these characteristics are consistently similar among isolates variations of MRSA. The study used 30 various isolates of MRSA belong to 13 spa types and 5 MLST types and determined the aggregation, the adherence, and the production of biofilms and slime for each isolate. The methods us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 15 publications
3
42
0
2
Order By: Relevance
“…The ability to produce biofilms was not dependent on SCCmec, but on the lineage. This is in agreement with the findings of Atshan and associates [29].…”
Section: Discussionsupporting
confidence: 94%
“…The ability to produce biofilms was not dependent on SCCmec, but on the lineage. This is in agreement with the findings of Atshan and associates [29].…”
Section: Discussionsupporting
confidence: 94%
“…Their results showed that biofilm formation on polystyrene surfaces was associated with CC8 strains. In a study published in 2012 by Atshan et al comparing phenotypic and genotypic characteristics of biofilm producing S. aureus strains, the most common biofilm producers belonged to CC8 (53.3%) followed by CC1 (20%), CC22 (16.7%), and CC7 (10%) [35]. Their results also showed that all 30 MRSA isolates carried out icaADBC, fnbA, eno, ebps, clfA, and clfB genes.…”
Section: Discussionmentioning
confidence: 90%
“…The chronic infections that cause by S. aureus, persist and increase the rate of morbidity and mortality in human population due to the development of biofilm structures produced by this pathogen (2). Biofilm forming bacteria are the cause of many nosocomial infections (3). According to some reports, over 65% of hospital-acquired infections occur by the infecting organisms that have the ability of producing biofilms (4).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore biofilm keeps bacteria out of reach of host immune defense mechanism and often resulting in persistent and difficult-to-treat infections (2,3). Methicillin resistant S. aureus (MRSA) that have the ability of biofilm formation can become resistant to the most currently use antibiotics (1).…”
Section: Introductionmentioning
confidence: 99%